PENGARUH VARIASI WAKTU PENGAPIAN DAN VOLUME LARUTAN ELEKTROLIT PADA ELEKTROLISER TERHADAP DAYA MESIN SUPRA X 125 TAHUN 2007 DAN PENERAPAN HASIL PENELITIAN PADA MATA KULIAH TEKNIK SEPEDA MOTOR - Yulanto, Dwiki Muda (Jurnal Nosel, 2015)
The aims of this research are to : (1) Find out the effect of using electrolyzer with variety of electrolyte volume to engine power Supra X 125 in 2007. (2) Find out the effect of modified ignition timing to engine power Supra X 125 in 2007. (3) Find out the effect of comparing electrolyte volume on electrolyzer and modified ignition timing to engine power Supra X 125 in 2007. (4) Find out the biggest engine power Supra X 125 in 2007 from comparing electrolyte volume on electrolyzer and modified ignition timing. This research was used experimental methods. The research was conducted at Mototech Motocourse Technology, Yogyakarta. The equipment that was used to measured engine power was Sportdyno V3.3. The population of this research was Supra X 125 in 2007 and the sample of this research was Supra X 125 in 2007 with JB51E1915937 engine number. This research was analyzed using descriptive data analysis. This research are using 3 variations ignition timing which are magnet with a standard ignition timing (150 BTDC), 20 and 40 advanced ignition timing. Variety of electrolyte volume, which are: 0 cc, 300 cc, and 500 cc volume electrolyte of electrolyzer. Based on the results of this study concluded that: (1) There was an increase engine power result consederation with on standard motorcycle. (2) There was an effect of modified ignition timing to engine power. Ignition timing 170 BTDC to result in engine power as big as 9.21 PS. Ignition timing 190 BTDC to result in engine power as big as 8.81 PS. (3) There was an interaction from comparing electrolyte volume on electrolyzer and modified ignition timing to engine power. Ignition timing 150 BTDC used electrolyzer with 300 cc and 500 cc electrolyte to result in engine power as big as 8.77 PS. Ignition timing 170 BTDC used electrolyzer with 300 cc electrolyte to result in engine power as big as 9.25 PS, although used electrolyzer with 500 cc electrolyte to result in engine power as big as 9.32 PS. Ignition timing 190 BTDC used electrolyzer with 300 cc electrolyte to result in engine power as big as 8.81 PS although used electrolyzer with 500 cc electrolyte to result in engine power as big as 8.94 PS. (4) Maximum engine power as big as 9.32 PS from using electrolyzer with 500 cc electrolyte and ignition timing 170 BTDC.